Ultrasound Strain Imaging to Assess the Biceps Brachii Muscle in Chronic Poststroke Spasticity. (5th February 2018) - Gao, Jing; Chen, Johnson; O'Dell, Michael; Li, Pai‐Chi; He, Wen; Du, Li‐Juan; Rubin, Jonathan M.; Weitzel, William; Min, Robert
Abstract : Objectives: The aim of the study was to assess the feasibility of ultrasound strain imaging in characterizing the biceps brachii muscle in chronic poststroke spasticity. Methods: We prospectively analyzed strain imaging data from bilateral biceps brachii muscles in 8 healthy volunteers and 7 patients with poststroke chronic spasticity. Axial deformations of the biceps brachii muscle and overlying subcutaneous tissue were produced by external compression using a sandbag (1.0 kg) attached to a transducer. The lengthening and shortening of the biceps brachii muscle and subcutaneous tissue were produced by manual passive elbow extension (from 90° to 0°) and flexion (from 0° to 90°), respectively. We used offline 2‐dimensional speckle tracking to estimate axial and longitudinal strain ratios (biceps brachii strain/subcutaneous tissue strain), and the longitudinal tissue velocity of the biceps brachii muscle. Statistical analyses included analysis of variance for testing differences in strain imaging parameters among healthy, nonspastic, and spastic biceps brachii muscles, the Bonferroni correction for further testing differences in US strain imaging among paired groups (healthy versus spastic, nonspastic versus spastic, and healthy versus nonspastic), and the Pearson correlation coefficient for assessing the intraobserver reliability of performing strain imaging in stroke survivors. Results: The differences in strain imaging parameters between healthy and spastic and between nonspastic and spastic biceps brachii muscles were significant at both 90° elbow flexion and maximal elbow extension ( P  < .01). There was no significant difference in axial strain ratios at 90° of elbow flexion or longitudinal tissue velocities between healthy and nonspastic muscles ( P  > .05). The intraobserver reliability of performing strain imaging in stroke survivors was good ( r  = 0.85; P  < .01). Conclusions: Ultrasound strain imaging seems to be feasible for characterizing the biceps brachii muscle in chronic poststroke spasticity.